Insight on the evolution and distinction of inclusive growth. Issue 4 (18th May 2016) - Biswas, Arindam
ABSTRACT: This article develops a new pragmatic approach in delineating inclusive growth, covering two issues. First, it records the chronological evolution of inclusive growth; second, it details the distinction between broad-based growth and pro-poor growth, and inclusive growth. The article aims to highlight the objectivity of inclusiveness, which is distinctly different than broad-based growth and pro-poor growth. The research concentrates on salient issues like growth, poverty, and inequality, identifies a distinct variation between broad-based growth/pro-poor growth and inclusive growth, and establishes the exclusivity of inclusive growth.